TO BE RELIGIOUS THROUH SUNDANESE SONG: : RELIGIOUS VALUES ON DU’A SONG BY NANO SURATNO TO STRENGHTEN EARLY CHILD CHARACTER IN ISLAMIC PERSPECTIVE - Lismarina, Lilis; Yuanita, M.Sn, Yenny; Nurannisa, S.Psi., M.Pd, Yulia (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2024)
Children's lives in the 21st century have generally changed in the religious aspect. It can be seen from the existence of some phenomenon, among them are that children cannot understand the values of the holy book in their life, frequent bullying among friends, misunderstanding the way of dressing, and so on. This is a challenge for educators especially teachers. One of the efforts to instill religious values can be done through music education at home. In this article, the author will analyze the religious values contained in a Sundanese song entitled Du'a by Nano Suratno. The aim of this article is to raise the awareness of the importance of religious values for children so that they have an excellent personality. The ground theories of this article are a theory of character education, development and personality of early childhood, music education, and religious theory in Islamic perspectives. The method of this article is descriptive analytic. The result shows tha the Du'a song contains two religious values such as iman (faith) and prayer. Those values are the indicators of ‘habluminallah’ (the relation between human with God). This article is expected to be one of references of learning model to strenght religious values through music.